A new species of Lepanthes (Pleurothallidinae) in honour "Bachué", the mythological mother of the indigenous Muisca people - Parra Sánchez, Edicson; Vieira Uribe, Sebastián; Moreno Silva, Juan Sebastian (2023)
During an expedition in which we randomly placed 341 plots across a large elevation range (1100-3880 m) and spatial gradient (~270 km) in the Eastern Cordillera, we found a new species of the genus Lepan-thes in Santuario de Fauna y Flora de Iguaque, Boyaca, Colombia. We propose L. bachue as a new species that is most similar to L. papallactae but it differs in its proliferous plants (vs. non proliferous), the petals with the upper lobe 2.5 mm long, the lower lobe 4.5 mm long, larger than the upper one, and the margins fimbriate (vs. lobes subequal, 4.5 mm long and shortly pubescent) and the lip with the blades oblong, sub-sigmoid, adnate to the middle of the column with a short oblong, bifid, an appendix hiding in the middle (vs. blades narrowly elliptical-oblong, adnate to the column above the middle with a recurved pedunculate, biglandular appendix). Our extensive sampling across different areas suggests that this species is geographically restricted and highly specialized in terms of habitat. Thus, it is urgent to protect its natural habitat and population.
En expediciones en la Cordillera Oriental, durante un muestreo aleatorio de 341 cuadrantes a lo largo de un amplio gradiente elevacional (1100-3880 m) y geográfico (~270 km), encontramos una especie nueva del género Lepanthes en el Santuario de Fauna y Flora de Iguaque, Boyacá, Colombia. Proponemos L. bachue como especie nueva similar a L. papallactae pero difiere por su crecimiento prolifero (vs. no pro-lifero), el lóbulo superior del labelo de 2.5 mm de largo, el lóbulo inferior 4.5 mm de largo, más largo que el lóbulo superior, y márgenes fimbriados (vs. lobulos de tamaño similar, 4.5 mm de largo cortamente pubescentes) y las láminas del labelo oblongas, sub-sigmoides, adnado a la mitad de la columna con un apéndice amarillo, corto, oblongo, bífido escondido en la mitad (vs. láminas estrechamente elíptico-oblongas, adnado a la mitad de la columna con un apéndice biglandular recurvado). Nuestro amplio muestreo, en términos de elevación y geográfico, evidencia que la nueva especie está geográficamente restringida al Santuario de Fauna y Flora de Iguaque presentando un alto nivel de especialización de hábitat, por tanto, es necesario proteger su hábitat natural y la población conocida hasta ahora.
Keywords: LEPANTHES -- IDENTIFICACION -- BOYACA (COLOMBIA); ORQUIDEAS -- BOYACA (COLOMBIA); ESPECIES -- IDENTIFICACION; PLANTAS ENDÉMICAS -- BOYACA (COLOMBIA); SANTUARIO DE FAUNA Y FLORA IGUAQUE (COLOMBIA)